Seeking American Society of Clinical Oncology‐Quality Oncology Practice Initiative (ASCO‐QOPI) certification in a northern New England rural health system and cancer care network - Hilary M. Perrey; Evelyn Taylor; Brett F. Cropp; Meaghan J. Bumpus; Shannon Lessard; Jeanette A. Pretorius; Jonathan H. Angus; Megan F. Duperreault; Amanda Snow; Dorothy Wang; Meredith Curtis; Lauren A. Couture; et al. (Wiley, 2024)
Abstract In 2006 following several years of preliminary study, the American Society of Clinical Oncology (ASCO) launched the Quality Oncology Practice Initiative (QOPI). This cancer‐focused quality initiative evolved considerably over the next decade‐and‐a‐half and is expanding globally. QOPI is undoubtedly the leading standard‐bearer for quality cancer care and contemporary medical oncology practice. The program garners attention and respect among federal programs, private insurers, and medical oncology practices across the nation. The MaineHealth Cancer Care Network (MHCCN) has undergone expansive growth since 2017. The network provides cancer care to more than 70% of the cases in Maine in a largely rural health system in Northern New England. In fall 2020, the MHCCN QOPI project leadership, following collaborative discussions with the ASCO‐QOPI team, elected to proceed with a health system-cancer network‐wide QOPI certification. Key themes emerged over the course of our two‐year journey including: (1) Developing a highly interprofessional team committed to the project; (2) Capitalizing on a single electronic medical record for data transmission to CancerLinQ; (3) Prior experience, especially policy development, in other cancer‐focused accreditation programs across the network; and (4) Building consensus through quarterly stakeholder meetings and awarding Continuing Medical Education (CME) and American Board of Medical Specialists (ABMS) Maintenance of Certification (MOC) credits to oncologists. All participants demonstrated a genuine spirit to work together to achieve certification. We report our successful journey seeking ASCO‐QOPI certification across our network, which to our knowledge is the first‐of‐its‐kind endeavor.